Construction of probe of the plant growth-promoting bacteria Bacillus subtilis useful for fluorescence in situ hybridization (2016)
Strains of Bacillus subtilis are plant growth-promoting bacteria (PGPB) of many crops and are used as inoculants. PGPB colonization is an important trait for success of a PGPB on plants. A specific probe, based on the 16 s rRNA of Bacillus subtilis, was designed and evaluated to distinguishing, by fluorescence in situ hybridization (FISH), between this species and the closely related Bacillus amyloliquefaciens. The selected target for the probe was between nucleotides 465 and 483 of the gene, where three different nucleotides can be identified. The designed probe successfully hybridized with several strains of Bacillus subtilis, but failed to hybridize not only with B. amyloliquefaciens, but also with other strains such as Bacillus altitudinis, Bacillus cereus, Bacillus gibsonii, Bacillus megaterium, Bacillus pumilus; and with the external phylogenetic strains Azospirillum brasilense Cd, Micrococcus sp. and Paenibacillus sp. The results showed the specificity of this molecular probe for B. subtilis. (C) 2016 Elsevier B.V. All rights reserved.